Prevalence and associated factors of herbal medicine use among pregnant women on antenatal care follow-up at University of Gondar referral and teaching hospital, Ethiopia: a cross-sectional study. Issue 1 (December 2017) - Mekuria, Abebe; Erku, Daniel; Gebresillassie, Begashaw; Birru, Eshetie; Tizazu, Balem; Ahmedin, Alima
Abstract Background Improving maternal and child health is one of the public health priorities in several African countries including Ethiopia. However, research on herbal medicine use during pregnancy is scarce in Ethiopia. The present study aimed at assessing the prevalence and correlates of herbal medicine use among pregnant women on antenatal care (ANC) follow-up at Gondar university referral hospital, Ethiopia Methods An institutional-based cross sectional study was conducted on 364 pregnant women attending ANC clinic from March to May 2016 at University of Gondar referral and teaching hospital, northwest Ethiopia. Data on socio-demography, pregnancy related information as well as herbal medicine use was collected through an interviewer-administered questionnaire. Descriptive statistics, univariate and multivariate logistic regression analysis were performed to determine prevalence and associated factors of herbal medicine use. Results From 364 respondents, 48.6% used herbal medicine during current pregnancy. ginger (40.7%) and garlic (19%) were the two most commonly used herbs in pregnancy. Common cold (66%) and inflammation (31.6%) were the most common reasons for herbal use. Majority of herbal medicine users (89.8%) had not consulted their doctors about their herbal medicine use. Rural residency (Adjusted odds ratio (AOR): 3.15, Confidence interval (CI): 1.17–6.14), illiteracy (AOR: 4.05, CI: 2.47–6.62) and average monthly income less than 100 USD (AOR: 3.08CI: 1.221–7.77) were found to be strong predictors of herbal medicine use. Conclusions The use of herbal medicine during pregnancy is a common practice and associated with residency, level of education and average monthly income. From the stand point of high prevalence and low disclosure rate, the health care providers should often consult pregnant women regarding herbal medicine use.